Effectiveness of Two-Year versus One-Year Use of Dual Antiplatelet Therapy in Reducing the Risk of Very Late Stent Thrombosis after Drug-Eluting Stent Implantation - Hamid Reza Poorhosseini; Seyed Kianoosh Hosseini; Tahereh Davarpasand; Masoumeh Lotfi Tokaldany; Mojtaba Salarifar; Seyed Ebrahim Kassaian; Mohammad Alidoosti; Younes Nozari; Ebrahim Nematipour; Ali Mohammad Haji Zeinali; Hasan Aghajani; Ali Reza Amirzadegan (Journal of Tehran University Heart Center, 2012)
Background: Impact of 12 months’ versus 24 months’ use of dual antiplatelet therapy on the prevalence of stent thrombosis in patients undergoing percutaneous coronary intervention (PCI) with the drug-eluting stent (DES) is not clear. As a result, duration of dual antiplatelet therapy is still under debate among interventionists.